Factors affecting physicians’ attitudes towards patient-centred care: a cross-sectional survey in Beijing - Talia Isaacs; Haiying Liang; Michael J Reiss (BMJ Open)
Objectives Patient-centred care has been raised as an important component in providing high-quality healthcare services. This research aims to measure physicians’ attitudes towards patient-centred care in Chinese healthcare settings and to identify the sociodemographic predictors of their attitudes using an exploratory research design.Design A cross-sectional survey.Setting Twelve hospitals in Beijing, China.Participants 1290 physicians from 12 hospitals in Beijing were invited to take part in the survey using snowball sampling methods. There was a response rate of 84% (n=1084), of which 1053 responses (82%) were valid and included in this research.Methods This research used a survey containing a previously validated 6-point Likert scale called ‘Chinese-revised Patient-Practitioner Orientation Scale’ (CR-PPOS). Descriptive statistics and multivariable logistic regression analyses were performed to measure participants’ attitudes and to identify the sociodemographic predictors of Chinese physicians’ attitudes towards patient-centred care.Results Gender, professional title (ie, seniority) and hospital type influence Chinese physicians’ attitudes towards patient-centred care. Female physicians, physicians with intermediate titles and those who work in tertiary (ie, top-level) hospitals tend to have higher patient-centred attitudes (OR=1.532, 95% CI 1.160 to 2.022; OR=2.089, 95% CI 1.206 to 3.618; OR=2.198, 95% CI 1.465 to 3.297) than male physicians with other titles, and than those who work in first, secondary or private hospitals. Physicians working in non-surgical departments, those who have received training in doctor–patient communication, and those who are satisfied with their income obtained high patient-centred scores, both on the overall CR-PPOS and its two subscales.Conclusions This research identified sociodemographic predictors of Chinese physicians’ attitudes towards patient-centred care. The findings contribute to knowledge of factors to be considered in reforming medical education and the Chinese healthcare system to improve physician–patient relationships and provide high-quality healthcare to patients. However, these findings are exploratory in nature and require further investigation to establish their validity and generalisability.